Dynamic Ultrasonography for Imaging Pediatric Fat Pad Herniation through the Lateral Patellar Retinaculum - Wei-Ting Wu; Ke-Vin Chang; Kuan-Wen Wu; Kamal Mezian; Vincenzo Ricci; Levent Özçakar (Diagnostics, 2022)
A 3-year-old boy was found to have a painless mass over his right anterior lateral knee for the previous 6 months. The mass was hardly identified during knee extension and became visible upon squatting. There was no specific finding on ultrasound imaging over his right knee at the supine extended position. During squatting, ultrasound imaging showed an ill-demarcated hyperechoic mass protruding next to the cartilage overlying the distal femur towards the subcutaneous layer through a slit over the lateral patellar retinaculum. Herniation of the fat pad through a defect in the lateral patellar retinaculum was diagnosed. Our case highlights the usefulness of ultrasound examination as regards the lateral patellar retinaculum defect in pediatric knees, as well as its capability for dynamic scanning to capture the exact “pathological moment”.